Analysis of the Impact of Pharmaceutical Waste on Water Quality and Bioremediation-Based Treatment Efforts - Nurul Arsy; Atiqa Kirana; Meilani; Fahira (Casuarina: Jurnal Teknik Lingkungan, 2026)
Pharmaceutical waste discharged into aquatic environments can significantly deteriorate water quality and disrupt ecosystems. Even at low concentrations, active pharmaceutical compounds may induce physiological changes in aquatic organisms and contribute to the emergence of antibiotic resistance. This study aims to analyze the impact of pharmaceutical waste on water quality and evaluate bioremediation using indigenous microorganisms as a sustainable treatment approach. Water samples contaminated with pharmaceutical residues were collected near healthcare facilities. Parameters such as pH, dissolved oxygen (DO), chemical oxygen demand (COD), and pharmaceutical concentrations were measured. Indigenous microorganisms capable of metabolizing pharmaceutical compounds were identified and applied in bioremediation experiments over 14 days. Results revealed a 50% reduction in pharmaceutical residues, accompanied by improved water quality indicators, including increased DO and decreased COD. The microorganisms demonstrated adaptability to polluted environments and utilized pharmaceutical compounds as energy sources. These findings underscore the potential of bioremediation as an eco-friendly strategy for pharmaceutical wastewater treatment. The study contributes to the development of sustainable waste management practices, emphasizing the role of local microbial resources in mitigating environmental pollution.